2022
DOI: 10.1182/blood.2022018052
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis of indeterminate potential and risk of death from COVID-19

Abstract: Two Letters to Blood address the risks of COVID-19 in populations with precursors of hematological disease. In the first article, Miller and colleagues report on whether clonal hematopoiesis of intermediate potential (CHIP) is associated with adverse outcomes with COVID-19, finding no association between CHIP and 28-day mortality while providing data indirectly linking IL-6 signaling and patient outcomes. In the second article, Ho and colleagues investigate the outcomes of patients with monoclonal gammopathy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In summary, we observed that the risk of COVID‐19 hospitalization increased with the presence of multiple or large (VAF ≥ 10%) CHIP clone(s) in this study of 470 Danish individuals, PCR‐confirmed positive for SARS‐CoV‐2 while 60–89 years old. These results are consistent with those of the large study by Kessler et al, 11 but not of the smaller one by Zhou et al 13 In the subset of 235 COVID‐19 hospitalized cases, we did not find CHIP to be a risk factor for ICU admission or in‐hospital death, in contrast to general admission, which is also consistent with findings by Duployez et al, 14 Hameister et al, 15 Petzer et al, 16 Miller et al, 12 and Del Pozo‐Valero et al 17 However, these results should be interpreted with caution as our study was designed as a matched case–control study between hospitalized and nonhospitalized COVID‐19. The previously observed association between PPM1D CHIP and severe COVID‐19 by Kessler et al 11 was only suggestively replicated in our data and may grant further investigation.…”
Section: Figuresupporting
confidence: 93%
“…In summary, we observed that the risk of COVID‐19 hospitalization increased with the presence of multiple or large (VAF ≥ 10%) CHIP clone(s) in this study of 470 Danish individuals, PCR‐confirmed positive for SARS‐CoV‐2 while 60–89 years old. These results are consistent with those of the large study by Kessler et al, 11 but not of the smaller one by Zhou et al 13 In the subset of 235 COVID‐19 hospitalized cases, we did not find CHIP to be a risk factor for ICU admission or in‐hospital death, in contrast to general admission, which is also consistent with findings by Duployez et al, 14 Hameister et al, 15 Petzer et al, 16 Miller et al, 12 and Del Pozo‐Valero et al 17 However, these results should be interpreted with caution as our study was designed as a matched case–control study between hospitalized and nonhospitalized COVID‐19. The previously observed association between PPM1D CHIP and severe COVID‐19 by Kessler et al 11 was only suggestively replicated in our data and may grant further investigation.…”
Section: Figuresupporting
confidence: 93%
“…DNA was extracted using Qiagen Mini kits Cat #27104 according to manufacturer's recommendations. We sequenced samples using a custom capture panel designed to tile known CH genes, targeting 600x read depth coverage as previously described 16 . Somatic mutations were called using publicly available methods in workflow description language in Mutect2 on the Terra Platform (https://terra.bio/).…”
Section: Dna Extraction and Ch Variant Callingmentioning
confidence: 99%
“…The more recent publications in this area similarly suggest that distinct biologic and clinical features of CH are relevant to its potential relationship with COVID-19. Studies by Zhou et al (55) and Miller et al (56) did not find associations between CH and risks of COVID-19 severity or mortality, respectively, when screening primarily for SNVs and indels of M-CH genes. The lack of association observed in these studies compared with that of Bolton et al (52) despite using similar sequencing methods may be attributable to their comparatively restricted gene panels, or the inclusion of cancer patients in the latter work contributing to an overall greater likelihood of detecting somatic variation (55, 56).…”
Section: Clonal Hematopoiesis May Influence Inflammation In Covid-19mentioning
confidence: 89%
“…Studies by Zhou et al (55) and Miller et al (56) did not find associations between CH and risks of COVID-19 severity or mortality, respectively, when screening primarily for SNVs and indels of M-CH genes. The lack of association observed in these studies compared with that of Bolton et al (52) despite using similar sequencing methods may be attributable to their comparatively restricted gene panels, or the inclusion of cancer patients in the latter work contributing to an overall greater likelihood of detecting somatic variation (55, 56). Nonetheless, these findings support a need to further explore whether mCA-CH or L-CH bear more influence on the clinical course of COVID-19 than conventional M-CH drivers.…”
Section: Clonal Hematopoiesis May Influence Inflammation In Covid-19mentioning
confidence: 89%